A Balance-Specific Exercise Intervention Improves Falls Risk but not Total Physical Functionality in Community-Dwelling Older Adults. (1st December 2014) - Smee, Disa J.; Berry, Helen L.; Waddington, Gordon S.; Anson, Judith M.
ABSTRACT Aims: The aim of this research was to investigate whether a simple balance-specific exercise simultaneously improves physical functionality and falls. Methods: Thirty-two community-dwelling individuals aged 65–92 years were assigned to either the control or wobble-board group. Participants were assessed pre- and postintervention using the Physiological Profile Assessment (a measure of falls risk) and the Continuous-Scale Physical Functional Performance-10 (a measure of physical functionality). Results: Participants in the intervention group, wobble-board training, had a decrease in their risk of falling by 36% (p = 0.009, ηρ2 = 0.396), while the control group recorded a slight but nonsignificant increase (6%). No change was seen in their total Continuous-Scale Physical Functional Performance-10 score. Conclusion: A balance-specific intervention decreased falls-risk and improved balance but not sufficiently to affect total physical functionality.